Exchanging challenge based learning experiences in the context of RoboSTEAM Erasmus+ Project - Conde, Miguel Ángel (2021)
In the context of the digital society, educational systems should prepare the students to succeed in a really volatile environment. In order to do so they require to acquire some specific competences that use to be related to STEAM Education. However, integrating STEAM is hard and requires of new methodologies and tools. RoboSTEAM is an Erasmus+ project that aims to facilitate this by using Challenge Based Learning and applying Physical Devices and Robotics. In order to know if what RoboSTEAM proposes work properly it must be tested in different contexts with different educational systems. The results of these tests should be compared, which requires of a common knowledge background. In order to achieve it RoboSTEAM proposes students and teachers exchanges between similar and different sociocultural environments, so they can learn how other people work in the project challenges and if what they do can be addressed by them in a similar way. The present work describes these exchanges, how they were planned and carried out and the main results obtained. From the exchanges carried out until now it is possible to say that they facilitate sharing knowledge that later can lead to better results in the project challenges and that they are enriching experiences both for students and for teachers.